2012
DOI: 10.1111/j.1865-1682.2012.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pattern Characterization of Cattle Naturally Infected by BTV-8

Abstract: Forty-one cattle from seven Belgian farms and two French farms confirmed as infected with bluetongue virus serotype 8 (BTV-8) were monitored from the onset of clinical signs to describe the disease pattern and estimate the duration of blood RT-qPCR and competitiveELISA positivity under field conditions. On each visit, blood samples were taken, and a standardized clinical form was filled in for each animal. A clinical score was calculated for every week until the end of clinical signs. A classification and regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
(37 reference statements)
2
24
0
Order By: Relevance
“…The consequence of this process is a set of fairly reliable estimates of the independent predictive accuracy of the tree, even when some of the data for independent variables are incomplete and/or comparatively small. Further details about CART are presented in previously published articles (e.g.,[8487][88]. …”
Section: Methodsmentioning
confidence: 99%
“…The consequence of this process is a set of fairly reliable estimates of the independent predictive accuracy of the tree, even when some of the data for independent variables are incomplete and/or comparatively small. Further details about CART are presented in previously published articles (e.g.,[8487][88]. …”
Section: Methodsmentioning
confidence: 99%
“…Importantly however, anecdotal observation suggested that changes had occurred in the epidemiology of the re‐emerging strain. Whereas the 2007–2009 BTV‐8 strain caused widespread clinical signs in cattle and sheep (Elbers, Spek, & Rijn, ; Zanella et al., ), the re‐emerging BTV‐8 strain has thus far only caused mild clinical illness (Sailleau et al., ). In addition, the rate of spread of the virus in France appeared slower than the original BTV‐8 strain.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 2006, severe disease was thought to be restricted to certain breeds of sheep and some species of deer, while other ruminants were considered mostly subclinically infected (Mellor & Boorman, ; Purse et al., ). Yet, cattle were strongly affected by the 2006/09 BTV‐8 outbreak in Western Europe (Zanella et al., ). BT surveillance and control are critical issues as its detection leads to trade restrictions with considerable economic impacts for exporter countries.…”
Section: Introductionmentioning
confidence: 99%